Tumor Microenvironment and Differential Responses to Therapy - Hirata, Eishu; Sahai, Erik (Cold Spring Harbor perspectives in medicine, 2017)
Cancer evolution plays a key role in both the development of tumors and their response to therapy. Like all evolutionary processes, tumor evolution is shaped by the environment. In tumors, this consists of a complex mixture of nontransformed cell types and extracellular matrix. Chemotherapy or radiotherapy imposes further strong selective pressures on cancer cells during cancer treatment. Here, we review how different components of the tumor microenvironment can modulate the response to chemo- and radiotherapy. We further describe how therapeutic strategies directly alter the composition, or function, of the tumor microenvironment, thereby further altering the selective pressures to which cancer cells are exposed. Last, we explore the consequences of these interactions for therapy outcomes and how to exploit our increasing understanding of the tumor microenvironment for therapeutic benefit.